Antonio Candido and David Viñas: Literary Criticism and the Closing of the Historical Past - Aguilar, Gonzaio (Literatura e Sociedade, 2009)
This text compares two seminal books in modern Latin American literary criticism: Antonio Candido’s Formação da literatura brasileira and Argentine critic David Viñas’ Literatura argentina y realidad política. Through a comparative analysis of their basic postulates, differences are assessed and the reasons for the notable dissimilarities between the Brazilian and the Argentine foundational books are explored.